2021
DOI: 10.5272/jimab.2021274.4084
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes for Septic Complications After Laparoscopic Appendectomy

Abstract: Purpose: The aim of the study is to investigate the postoperative infectious complications after laparoscopic appendectomy of patients with acute appendicitis in UMHATEM "N.I.Pirogov". Material and Methods: For a period of one year from 1.1.2018 to 31.12.2018. a total of 218 patients with acute appendicitis were operated in the General, Visceral and Emergency Surgery Department of UMHATEM "Pirogov". Of these, 143 were laparoscopic apendectomy. Indicators characterizing basic clinical and pathological features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
1
2
1
Order By: Relevance
“…These results are consistent with previous data from Lee et al, although a longer LOS was only observed comparing complicated appendicitis and negative appendectomy [18]. The overall complication rate after appendectomy for acute appendicitis in our study was 6% and therefore consistent with previous data from literature [10][11][12][13][14]. We could identify six independent risk factors for morbidity: higher age, higher preoperative WBC count, higher preoperative CRP, lower preoperative hemoglobin, longer time to surgery and longer duration of surgery.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with previous data from Lee et al, although a longer LOS was only observed comparing complicated appendicitis and negative appendectomy [18]. The overall complication rate after appendectomy for acute appendicitis in our study was 6% and therefore consistent with previous data from literature [10][11][12][13][14]. We could identify six independent risk factors for morbidity: higher age, higher preoperative WBC count, higher preoperative CRP, lower preoperative hemoglobin, longer time to surgery and longer duration of surgery.…”
Section: Discussionsupporting
confidence: 93%
“…In our cohort, about half of patients with postoperative complications had major morbidity (Clavien-Dindo III-V). This rate was slightly higher than those reported in literature [11,12,14,21,23]. On the other side, mortality was 0.13% in our study group, which is lower than reported by two big European analysis with over 100,000 patients (mean mortality of 2.1-2.4 per 1000 patients) [24,25].…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations